Overcoming Senior High School Students' Misconceptions on Newton's Laws: A DSLM with Inquiry Learning based Computer Simulations - Fratiwi, N. J.; Samsudin, A.; Kaniawati, I.; Suhendi, E.; Suyana, I.; Hidayat, S. R.; Zulfikar, A.; Sholihat, F. N.; Setyadin, A. H.; Amalia, S. A.; Jubaedah, D. S.; Muhaimin, M. H.; et al. (IOP PUBLISHING LTD, 2019)
Now a day, several problems regarding the misconceptions still occurred in the physics learning, especially in mechanical concept, such as Newton's Laws. The aim of this research is to overcome students' misconceptions on Newton's Laws through combining Dual-Situated Learning Model (DSLM) and inquiry learning based computer simulations. The research has been utilized the ADDIE model, stands for Analyzing, Designing, Developing, Implementing and Evaluating. The subjects who involved in the research are 20 senior high school students (10 boys and 10 girls, their ages were an average of 16 years-old). The instrument used in this research is eight question of Four-Tier Newtonian Test (FTNT). At the developing phase, we have been developing the Dual-Situated Learning Model (DSLM) which is combined with inquiry learning based computer simulations. At the evaluating phase, we obtained the data about students' misconceptions of forces concepts are decreased sharply. To sum up, the combining DSLM and inquiry learning based computer simulations are effective to overcome the misconceptions of senior high school students on Newton's Laws.
Keywords: CONCEPTUAL CHANGE; IDEAS; Physics